Estimation of genetic parameters and correlations for growth, rooting and frost tolerance in Eucalyptus grandis x Eucalyptus nitens hybrids - Brink, Willie Andries (Stellenbosch : Stellenbosch University, 2023)
Brink, W. A. 2023. Estimation of genetic parameters and correlations for growth, rooting and frost tolerance in Eucalyptus Grandis x Eucalyptus Nitens hybrids. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0864975d-594a-4e1e-86db-3d640282d144